Early seizures predict the development of epilepsy in children and adolescents with stroke. (May 2017) - Breitweg, Ina; Stülpnagel, Celina von; Pieper, Tom; Lidzba, Karen; Holthausen, Hans; Staudt, Martin; Kluger, Gerhard
Abstract: Purpose: To identify risk factors for the development of epilepsy after pediatric stroke. Methods: Retrospective analysis of hospital charts of 93 children and adolescents with post-neonatal non-traumatic stroke and a minimum follow-up of two years. Seizures during the first 48 h after onset of stroke symptoms were defined as "early seizures"; when two or more seizures occurred after this period, the patient was classified as "epileptic". Results: Early seizures, young age at stroke and MRI evidence of cortical involvement were observed more frequently in the children who developed epilepsy. These factors were, however, significantly interrelated; a stepwise multiple regression analysis in 46/93 patients with complete datasets identified only the occurrence of early seizures as a significant risk factor: 15/19 (79%) children with early seizures developed epilepsy, as opposed to only 7/53 (13%) without early seizures. Conclusion: Children with stroke who show seizures during the first 48 h after onset of stroke symptoms have a high risk to develop post-stroke epilepsy, whereas in children without early seizures, post-stroke epilepsy is rare. Highlights: Identification of risk factors for epilepsy (E) after post-neonatal pediatric stroke. Retrospective analysis of 93 children with post-neonatal non-traumatic stroke. Early seizures, young age, cortical involvement on MRI more frequently with E. Stepwise multiple regression analysis in 46/93 patients with complete datasets. Identification of only early seizures as significant risk factor.